The Role of Resveratrol in Mammalian Reproduction - Rolando Pasquariello (Molecules, 2020)
Resveratrol is one of the most investigated natural polyphenolic compounds and is contained in more than 70 types of plants and in red wine. The widespread interest in this polyphenol derives from its antioxidant, anti-inflammatory and anti-aging properties. Several studies have established that resveratrol regulates animal reproduction. However, the mechanisms of action and the potential therapeutic effects are still unclear. This review aims to clarify the role of resveratrol in male and female reproductive functions, with a focus on animals of veterinary interest. In females, resveratrol has been considered as a phytoestrogen due to its capacity to modulate ovarian function and steroidogenesis via sirtuins, SIRT1 in particular. Resveratrol has also been used to enhance aged oocyte quality and as a gametes cryo-protectant with mainly antioxidant and anti-apoptotic effects. In males, resveratrol enhances testes function and spermatogenesis through activation of the AMPK pathway. Furthermore, resveratrol has been supplemented to semen extenders, improving the preservation of sperm quality. In conclusion, resveratrol has potentially beneficial effects for ameliorating ovarian and testes function.